Epistemologi islam dan fikih arsitektur: Integrasi pendidikan arsitektur dengan material bambu sebagai solusi ramah lingkungan - Hardiansyah, Nur (Maliki Interdisciplinary Journal, 2025)
The integration of Islamic epistemology and architectural fiqh in architectural education provides a strong philosophical, ethical, and spiritual foundation for creating a sustainable architectural paradigm. Tawhid (divine unity), reason, revelation, and empirical experience serve as the basis for developing creativity, innovation, and social as well as environmental responsibility. Architectural fiqh, through the concept of maqāṣid al-sharī‘ah, emphasizes the importance of public benefit (maṣlaḥah), environmental protection (ḥifẓ al-bī’ah), and the preservation of civilization (ḥifẓ al-‘umrān) as guiding principles in design decision-making. Meanwhile, bamboo aligns with the principles of maqāṣid al-sharī‘ah and sustainability due to its rapid growth, strength, flexibility, and low carbon emissions. Beyond its technical aspects, bamboo also provides spatial and temporal experiences with philosophical and spiritual significance. An architectural curriculum that integrates Islamic values and sustainability can utilize bamboo as a case study through interdisciplinary learning approaches and life-based studio laboratories. However, the low level of student awareness regarding the technical and social dimensions of bamboo requires more intensive teaching strategies through research, collaboration, and community engagement. Thus, the integration of Islamic epistemology, architectural fiqh, and bamboo as a sustainable material is expected to foster an architectural education that not only emphasizes technical competence but also enhances ecological, ethical, and spiritual awareness in achieving social welfare.